2020
DOI: 10.1007/s11548-020-02247-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of manual versus robot-assisted contralateral gate cannulation in patients undergoing endovascular aneurysm repair

Abstract: PurposeRobotic endovascular technology may offer advantages over conventional manual catheter techniques. Our aim was to compare the endovascular catheter path-length (PL) for robotic versus manual contralateral gate cannulation during endovascular aneurysm repair (EVAR), using video motion analysis (VMA). MethodsThis was a multicentre retrospective cohort study with fluoroscopic video recordings of 24 EVAR cases (14 robotic, 10 manual) performed by experienced operators (>50 procedures), obtained from four le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Robotic systems in interventional procedures also have the potential for more practical interventions and improved outcomes. Although robotic systems are generally thought to decrease procedural times, Cheung et al and Weinberg et al have demonstrated that this is not always true, primarily owing to increased robotic cannulation times and a lack of operator familiarity with the robotic system [44,54]. However, learning curves are expected in every field, and as providers become more experienced with robotics, this trend may improve as has been shown in other domains of surgical medicine [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic systems in interventional procedures also have the potential for more practical interventions and improved outcomes. Although robotic systems are generally thought to decrease procedural times, Cheung et al and Weinberg et al have demonstrated that this is not always true, primarily owing to increased robotic cannulation times and a lack of operator familiarity with the robotic system [44,54]. However, learning curves are expected in every field, and as providers become more experienced with robotics, this trend may improve as has been shown in other domains of surgical medicine [55].…”
Section: Discussionmentioning
confidence: 99%
“…Ten articles describe the role of AI/robotics-based treatment of neurovascular disorders [14][15][16][17][18][43][44][45][46][47]. Table 2 shows a description of the results of these studies.…”
Section: Ai-based Treatment Of Cerebrovascular Disordersmentioning
confidence: 99%
“…But up to date, in vivo experience in robotic-assisted endovascular aortic repair is limited to aortic arch catheter placement during TEVAR [ 43 ], contralateral gate cannulation in EVAR [ 51 ], and cannulations of renal or mesenteric arteries during FEVAR [ 52 ]. Manual intervention is still necessary, but with future technical progress and by combining the robot with three-dimensional fusion imaging technology, these challenging procedures may be performed with little radiation and contrast use, thus significantly improving patients’ safety as well as the surgeon’s radiation exposure.…”
Section: Robot-assisted Endovascular Surgerymentioning
confidence: 99%